Pengaruh Jenis Umpan Terhadap Hasil Tangkapan Ikan Gabus (Channa striata) pada bubu di Perairan Rawa Kampung Wasur - Pane, Lindon Robinson; Merly, Sendy Lely; Sakap, Enos; Dumatubun, Nelly; Mappasessu, Baso; Bokowi, Dom Jimi (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
The potential of fisheries resources in Merauke Regency is very high, both in marine and inland including swamp waters. However, swamp waters in this Regency are relatively low to be utilized. This research was held in Swamp Ecosystem located in Wasur Village, Merauke Regency. The purpose of this study was to determine the effect of the various types of bait on the catch of fish, especially Snakehead fish by using one type of fishing gear known as traps. The benefit is to be able to provide additional information to the public about the type of bait most favored by Snakehead. This study used experimental fishing methods and further analyzed using a completely randomized design with three different bait treatment types: ants, frogs, and worms. The results showed that the percentage of fish caught using ant bait reached 53%, followed by frog bait at 28%, and worm bait at 19%, respectively. Overall, this research reveals that ant is the most preferred bait by Snakehead fish compared with two other baits.